Backstepping Adaptive Fuzzy Scheme for SCARA GRB400 Robot - Wei Yong Qiao (Institute of Advanced Engineering and Science, 2013)
In order to achieve the accurate trajectory tracking of 2 degree-of –freedom robot, a backstepping adaptive fuzzy control scheme based on Lyapunov method, is presented for the SCARA (Selective Compliance Assembly Robot Arm) robot system. The control strategy consists of the traditional backstepping control and adaptive fuzzy control to cope with the model unknown and parameter disturbances. The system is modeled using the MATLAB-SIMULINK toolbox. The simulation is presented to verify the effectiveness of the proposed control scheme. From the simulation results, fast response, strong robustness, good disturbance rejection capability and good angle tracking capability can be obtained. The output tracking error between the actual position output and the desired position output can asymptotically converge to zero. It is also revealed from simulation results that the proposed control strategy is valid and effective for the SCARA robot system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.2634